REVIEW ON THEORY AND EVIDENCE OF POVERTY, GROWTH, AND INEQUALITY - Papadaskalopoulos, Athanassios; Korres, George M.; Polychronopoulos, George (Journal of European Economy, 2018)
How is inequality generated and how it reproduces over time? This has been a major concern of sociology scientists for more than a century. The changes in aggregate or average income is a good measure for economic growth but is far from being the only one. There is an increasing «inequality» throughout the world. Over the period 1960-2000, averaged per-capita income in the richest 5% of the world’s nations was about twenty-nine times the corresponding figure for the poorest 5%. Poverty also affects other forms of economic and social functioning. The measurement of poverty is based on the notion of poverty line which is constructed from monetary estimates of minimum needs.